High Energy Density Welding of Ni-Based Superalloys: An Overview - Riccardo Donnini; Alessandra Varone; Alessandra Palombi; Saveria Spiller; Paolo Ferro; Giuliano Angella (Metals)
High energy density technologies for welding processes provide opportune solutions to joint metal materials and repair components in several industrial applications. Their high-performance levels are related to the high penetration depth and welding speed achievable. Moreover, the localized thermal input helps in reducing distortion and residual stresses in the welds, minimizing the extension of the fusion zone and heat-affected zone. The use of these welding technologies can be decisive in the employment of sophisticated alloys such as Ni-based superalloys, which are notoriously excellent candidates for industrial components subjected to high temperatures and corrosive work conditions. Nonetheless, the peculiar crystallographic and chemical complexity of Ni-based superalloys (whether characterized by polycrystalline, directionally solidified, or single-crystal microstructure) leads to high susceptibility to welding processes and, in general, challenging issues related to the microstructural features of the welded joints. The present review highlights the advantages and drawbacks of high energy density (Laser Beam and Electron Beam) welding techniques applied to Ni-based superalloy. The effects of process parameters on cracking susceptibility have been analyzed to better understand the correlation between them and the microstructure-mechanical properties of the welds. The weldability of three different polycrystalline Ni superalloys, one solid solution-strengthened alloy, Inconel 625, and two precipitation-strengthen alloys, Nimonic 263 and Inconel 718, is reviewed in detail. In addition, a variant of the latter, the AF955 alloy, is also presented for its great potential in terms of weldability.